STUDI KUALITATIF: PENGALAMAN COMMUNITY LEADERS DALAM PENCEGAHAN DEMAM BERDARAH DENGUE - I Ketut Swarjana; Anak Agung Istri Wulan Krisnandari (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2013)
The Incidence Rate (IR) of dengue hemorrhagic fever has increased sharply. Indonesia is the country with the highest incidence rate of dengue in South East Asia. Denpasar municipality and Badung regency have the highest incidence rate of dengue in Bali. Community leaders hold an important role in decreasing the IR.This research aimed to explore the community leaders’ experiences in preventing dengue.This study was a qualitative research with a phenomenology approach. Participants of this study included five community leaders from Pererenan Village, Mengwi District, Badung Regency.Six themes assessed in this study included: 1) Inadequate knowledge of dengue vectors; 2) Perspectives in the prevention of dengue; 3) Low community participation; 4) The combination of prevention methods; 5) Inadequate coordination; and 6) Poor follow-up.Knowledge, participation, empowerment of the community, and the coordination between stakeholders including community, community leaders and health sectors holds an important role in the prevention of dengue.